PATTERN RECOGNITION OF ISLANDING DETECTION USING TT-TRANSFORM - Khamis, Aziah (2012)
Islanding is a condition where a part of the distribution system becomes electrically isolated from the remainder of the power system. The islanding detection for distributed generation (DG) units becomes an important issue in power system where the DG installations must be managed and protected during the islanded mode of operation. This paper proposed a new signal processing technique by introducing TT-transform in detecting islanding condition. This proposed method can detect the islanding condition by extracting the features of the voltage signals from the targeted DG location. The proposed technique has been simulated and analyzed in SimPowerSystem/MATLAB® simulation software. The results of the three-phase fault and islanding event were represented using 2D TT transformed plots of the original signals. The finding shows that each event case has a unique pattern so that it is possible to detect islanding conditions with accurate and faster manner.